The impact of FTAs on MENA exports of intermediate and final goods - Adriana R. Cardozo; Inmaculada Martínez-Zarzoso; Paula L. Vogler (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
This paper is the first to analyze the impact of free trade agreements (FTAs) and the harmonization of rules of origin (RoO) on Middle East and North African (MENA) countries' exports differentiating between final and intermediate goods for a global sample of trade partners. Data on exports from four MENA countries (Egypt, Jordan, Morocco and Tunisia) to 61 destinations over the period 1995-2016 are used to estimate a structural gravity model applying a Poisson Pseudo Maximum Likelihood (PPML) estimator. Moreover, the paper estimates the effect of the progressive adoption of the Pan-European-Mediterranean RoO. Results show that FTAs have been overall successful in increasing MENA exports. This is particularly truefor FTAs that eliminate protection on agricultural products. In contrast to the existing literature, we find that the agreements concluded with European countries raise MENA exports, whereas no significant impact is found for the application of the Pan-European RoO.
Keywords: F10; 330; gravity model; FTA; MENA; PPML; panel data